Episodic deposition of stalagmites in the northeastern Democratic Republic of the Congo suggests Equatorial Humid Periods during insolation maxima. (15th June 2022) - Dupont, Laura A.; Railsback, L. Bruce; Liang, Fuyuan; Brook, George A.; Cheng, Hai; Edwards, R. Lawrence
Abstract: Matupi Cave, near the equator at 1.2°N in the northeastern Democratic Republic of the Congo, is in an inland region of equinoctial (March–May and August–November) rainfall distinct from summer rainfall to the north (e.g., in the Sahara) and to the south. Investigation of one entire stalagmite, parts of two others, and a core through a fourth from Matupi reveals stalagmite growth, and faster deposition, during two periods at ∼18.1 to ∼13.4 and ∼9.2 to 3.1 ka, with stalagmite deposition ending at 3.1 ka during a transition to drier conditions. The two periods of inferred wetter conditions at Matupi coincide with the two maxima in equatorial insolation over the most recent 25 kyr. The inferred periods of wetness extend earlier and later than the North African Humid Period, which resulted from a maximum in solstitial (June) insolation at 11–12 ka rather than equinoctial (March or September) insolation at 6 and 17 ka. Matupi's pattern of two wet periods that are coincident with maxima in equatorial insolation over the most recent 25, 000 years is also seen in a paleoclimate record from inland equatorial South America (and earlier periods of wetness in that record coincide with earlier maxima in equatorial insolation). The two records combine to suggest the concept of insolation-driven Equatorial Humid Periods at ∼11-kyr intervals, analogous to – but distinct in long-term timing and in seasonality of rainfall from – the more familiar North African Humid Periods recognized across the Northern Hemisphere from roughly 10°N to 25°N. Highlights: Four stalagmites from Matupi Cave in Democratic Republic of the Congo examined. Wet periods not coeval with (North) African Humid Period known from northern Africa. Results suggest Equatorial Humid Periods during maxima in equatorial insolation. Most recent Equatorial Humid Periods were at insolation maxima at ∼6 and ∼17 ka. Equatorial Humid Periods also evident in stalagmites from 3°S in Amazonian Ecuador.